2013
DOI: 10.1242/dev.087585
|View full text |Cite
|
Sign up to set email alerts
|

De novoDNA methylation of endogenous retroviruses is shaped by KRAB-ZFPs/KAP1 and ESET

Abstract: SUMMARYEndogenous retroviruses (ERVs) undergo de novo DNA methylation during the first few days of mammalian embryogenesis, although the factors that control the targeting of this process are largely unknown. We asked whether KAP1 (KRAB-associated protein 1) is involved in this mechanism because of its previously defined role in maintaining the silencing of ERVs through the histone methyltransferase ESET and histone H3 lysine 9 trimethylation. Here, we demonstrate that introduced ERV sequences are sufficient t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
135
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(148 citation statements)
references
References 71 publications
(129 reference statements)
12
135
1
Order By: Relevance
“…Cold Spring Harbor Laboratory Press on May 9, 2018 -Published by genesdev.cshlp.org Downloaded from H3K9 trimethylation, and HP1 recruitment, with DNA methylation occurring only secondarily to ensure the permanence of the silencing process (Quenneville et al 2012;Rowe et al 2013a). Our observation that KB murine L1 elements are up-regulated upon Setdb1 knockout in mES cells confirms the primary importance of histone methylation-based mechanisms in their control.…”
Section: Krab-kap1 Controls L1 In Es Cells Genes and Development 1405supporting
confidence: 68%
See 1 more Smart Citation
“…Cold Spring Harbor Laboratory Press on May 9, 2018 -Published by genesdev.cshlp.org Downloaded from H3K9 trimethylation, and HP1 recruitment, with DNA methylation occurring only secondarily to ensure the permanence of the silencing process (Quenneville et al 2012;Rowe et al 2013a). Our observation that KB murine L1 elements are up-regulated upon Setdb1 knockout in mES cells confirms the primary importance of histone methylation-based mechanisms in their control.…”
Section: Krab-kap1 Controls L1 In Es Cells Genes and Development 1405supporting
confidence: 68%
“…In human embryonic stem (hES) and mouse ES (mES) cells, the KRAB-ZFP-mediated docking of KAP1 at EREs triggers the formation of heterochromatin through the recruitment of the SETDB1 (also known as ESET) histone methyltransferase, responsible for trimethylating histone 3 at Lys9; histone deacetylases; and HP1 (heterochromatin protein 1), which collectively induce transcriptional repression (Schultz et al 2002;Ivanov et al 2007). The further recruitment of DNA methyltransferases (DNMTs) results in permanent silencing marks, which are subsequently maintained throughout development without need for persistent expression of sequence-specific ERErecognizing repressors (Quenneville et al 2012;Rowe et al 2013a).…”
mentioning
confidence: 99%
“…4E), but such drastic decreases were not observed in OCT3/4-or SOX2-binding to LINE-1. Two proteins, KAP-1 (KRABassociated protein 1) and histone methyltransferase SET domain bifurcated 1 (ESET), have been shown to be critical in suppression of endogenous retroviruses (16). ChIP experiments revealed that in HDFs transduced with OSKM, the binding of KAP-1 to LTR7s significantly decreased in ABHD12B and HHLA1 loci, but this decrease was not observed with OSM or OSNM (OSM with NANOG instead of KLF4) (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…In murine ES cells, TRIM28-induced repression leads to DNA methylation, which is thought to result in permanent silencing of EREs (Quenneville et al 2012;Rowe et al 2013a). We thus examined the methylation status of EREs in human ES cells by correlating publicly available ENCODE (Encyclopedia of DNA Elements) Project DNA methylation data with our TRIM28 ChIP-seq results.…”
Section: Interdependence Between Trim28 Ere Recruitment and Dna Methymentioning
confidence: 99%